2011
DOI: 10.1002/hed.21910
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the management of recurrent or metastatic squamous cell carcinoma of the head and neck

Abstract: Most patients with locally advanced squamous cell carcinoma of the head and neck (SCCHN) undergo definitive therapy, yet locoregional recurrence and metastasis are common. Most patients ultimately require systemic treatment. Platinum/5-fluorouracil (5-FU) has been the standard of care for patients with good performance status (median survival, 6-8 months). Cetuximab, a monoclonal antibody against epidermal growth factor receptor (EGFR), significantly improved median survival in combination with platinum/5-FU c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 149 publications
1
33
0
1
Order By: Relevance
“…Studies that only included OSCC in their evaluation show a comparably smaller number of HPV+ SCC, similar to this study [36, 37]. However, studies focusing on OPSCC, especially tonsil SCC, have higher HPV positivity rates [38] because the virus interacts with lymphoid tissue. The HPV has a selective tropism for the epithelium lining the tonsillar crypts.…”
Section: Discussionsupporting
confidence: 76%
“…Studies that only included OSCC in their evaluation show a comparably smaller number of HPV+ SCC, similar to this study [36, 37]. However, studies focusing on OPSCC, especially tonsil SCC, have higher HPV positivity rates [38] because the virus interacts with lymphoid tissue. The HPV has a selective tropism for the epithelium lining the tonsillar crypts.…”
Section: Discussionsupporting
confidence: 76%
“…26 Some oral cancers may originate from precancerous lesions with epithelial dysplasia. 27,28 Previous studies also reported that oral of incubation, were assayed by MTT and LDH.…”
Section: Discussionmentioning
confidence: 99%
“…2 Surgical management is usually the primary therapy for this disease, although radiation and chemotherapy also have prominent roles. 3 …”
Section: Introductionmentioning
confidence: 99%